2011
DOI: 10.4103/0971-9784.81570
|View full text |Cite
|
Sign up to set email alerts
|

Role of multimodality cardiac imaging in preoperative cardiovascular evaluation before noncardiac surgery

Abstract: The preoperative cardiac assessment of patients undergoing noncardiac surgery is common in the daily practice of medical consultants, anesthesiologists, and surgeons. The number of patients undergoing noncardiac surgery worldwide is increasing. Currently, there are several noninvasive diagnostic tests available for preoperative evaluation. Both nuclear cardiology with myocardial perfusion single photon emission computed tomography (SPECT) and stress echocardiography are well-established techniques for preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…1 Although, the value of medical consultation in preoperative risk evaluation seems to be imperative, investigations have nevertheless questioned the effectiveness of preoperative assessment. 2 Therefore, the development of an accurate and practical test that will provide timely assistance to surgeons, cardiologists, anesthesiologists and patients is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although, the value of medical consultation in preoperative risk evaluation seems to be imperative, investigations have nevertheless questioned the effectiveness of preoperative assessment. 2 Therefore, the development of an accurate and practical test that will provide timely assistance to surgeons, cardiologists, anesthesiologists and patients is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, if patients are unable to perform adequate exercise, pharmacological stress with adenosine, dipyridamole, or dobutamine stress myocardial perfusion scintigraphy with single photon computed tomography or dobutamine echocardiography are recommended. 25,26 But stress myocardial perfusion scintigraphy and dobutamine echocardiography have several limitations such as lack of facility, limited expertise, nondiagnostic or nonconclusive results, and expense. It is here that coronary computed tomography angiography (CCTA) with multidetector computed tomography becomes useful as CCTA has demonstrated excellent delineation of coronary artery stenosis.…”
Section: Approach To Noncardiac Surgery In a Cardiac Patient: Do We Nmentioning
confidence: 99%
“…Demographic and clinical characteristics were similar in both groups, except for systolic arterial pulmonary pressure in the HES group v 25 mmHg [extremes [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in the NaCl group; p = 0.017). We found a moderate but significant decrease in additional fluids mandatory to maintain hemodynamic stability and adequate functioning during CPB in the HES group (Table 1).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Therefore, CMR has recently been used more frequently in clinical practice as a preoperative test for myocardial viability and perfusion, valvular heart disease, cardiomyopathy, and congenital heart disease. 82) In particular, in patients who showed a negative stress perfusion CMR examination, the probability of not experiencing cardiac death or a nonfatal myocardial infarction for at least 3 years is as high as 99.2%, indicating a very low likelihood of future cardiovascular disease. 37) Additionally, in meta-analysis of 21 studies that observed a total of 1233 subjects, stress perfusion CMR examination scored high on its ability to assess obstructive CAD with a sensitivity of 84% (range, 44-93%) and a specificity of 80% (range, 60-100%); therefore, CMR is thought to be very useful in the preoperative assessment of CAD.…”
Section: )77)81)mentioning
confidence: 99%